2016
DOI: 10.1111/eva.12409
|View full text |Cite
|
Sign up to set email alerts
|

Increases in the mean and variability of thermal regimes result in differential phenotypic responses among genotypes during early ontogenetic stages of lake sturgeon (Acipenser fulvescens)

Abstract: Climate change is affecting thermal conditions worldwide. Understanding organismal responses associated with predicted changes are essential for predicting population persistence. Few studies have examined the effects of both increased mean and variance in temperature on organismal traits, particularly during early life stages. Using lake sturgeon (Acipenser fulvescens) from Black Lake, MI, we tested whether phenotypic variation differed among families reared in two constant (10 and 18°C) and two fluctuating‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 74 publications
(119 reference statements)
3
22
1
Order By: Relevance
“…These results were similar to other studies that found differences in alevin mass were largely driven by family or population, as opposed to temperature treatment (Burt et al, 2012;Hendry et al, 1998;Whitney et al, 2014). Our findings were inconsistent with other studies (Burt et al, 2012;Drinan et al, 2012;Haugen & Vøllestad, 2000;Hendry et al, 1998) There is increasing interest in understanding the role of the timing of temperature delivery to developing embryos beyond consideration of average temperatures (Dammerman et al, 2016;Fuhrman et al, 2017;Steel et al, 2012;Tillotson, 2015). In a series of common garden experiments, Murray and Beacham (1987) Tillotson, 2015).…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…These results were similar to other studies that found differences in alevin mass were largely driven by family or population, as opposed to temperature treatment (Burt et al, 2012;Hendry et al, 1998;Whitney et al, 2014). Our findings were inconsistent with other studies (Burt et al, 2012;Drinan et al, 2012;Haugen & Vøllestad, 2000;Hendry et al, 1998) There is increasing interest in understanding the role of the timing of temperature delivery to developing embryos beyond consideration of average temperatures (Dammerman et al, 2016;Fuhrman et al, 2017;Steel et al, 2012;Tillotson, 2015). In a series of common garden experiments, Murray and Beacham (1987) Tillotson, 2015).…”
Section: Discussioncontrasting
confidence: 65%
“…Other studies (Beacham & Murray, 1989;Haugen & Vøllestad, 2000;Kinnison, Unwin, Hershberger, & Quinn, 1998;Wood & Fraser, 2015) that focused on population-level differences also found a similar lack of genetic differences in hatch timing in regimes representing natural conditions (but see Jensen et al, 2008;Whitney et al, 2014). We expected to observe population differences while others did not because of the inclusion of fluctuating thermal regimes, which has produced significant population (Fuhrman et al, 2017) and family-level differences (Dammerman et al, 2016;Steel et al, 2012;Tillotson, 2015). Furthermore, we expected this because we used populations that use a shared rearing environment later during their early life history and we expected their phenology, even with very different developmental thermal regimes, to generally synchronize given their shared recipient environment.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations